La genèse de l’article 64 du code pénal - Laurence Guignard (Criminocorpus)
This article deals with the creation of the penal Code article 64. It analyses the debates, which permitted elaboration of its doctrinal, case law and procedural. The article introduces a set of documents reporting legislative debates between 1791 and 1810. The whole file shows that a lot of difficulties met later, during the 19th C, by the new system founded on penal irresponsibility, civil incapacity and medicalization of madness, had been anticipated in a very precise and concrete way by the discussions of revolutionary and imperial period.For instance, legal definition of insanity or of competent authority (magistrates, experts, group of wise men), detention of insane, or therapeutic order for those who would have been considered as penally irresponsible were hard-debatted, but wise assemblies preferred not to decide anything.